The Courts of Cádiz and the Constitution of 1812 in the Progressive Historiography of 19th Century - Vilches García, Jorge (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
This paper analyzes how the interpretation of Spanish History was constructed by progressive writers between 1854 and 1880. It focuses specifically on the ‘Cadiz Cortes’ (parliament) and the Constitution of 1812 and their use as arguments of political opposition against other parties, and finally, the Bourbons.